Development of a novel boron carbide-based coating material for reduction of activation in neutron application facilities. (March 2022) - Tanaka, Seiichiro; Okuno, Koichi; Takeuchi, Yukiko; Tabara, Takashi
Abstract: Recently, neutrons have been studied for application in various fields such as the structural analysis of crystals, non-destructive inspection of infrastructures, and boron neutron capture therapy (BNCT). However, the neutron activation of concrete in accelerator facilities has caused problems whereby the workers are exposed to radiation and the disposal cost of radioactive waste increases at the time of decommissioning of these facilities. Hence, in the present study, a novel coating material using boron carbide (B4 C) was developed to reduce the activation of concrete and other materials. Its low activation effect was evaluated through neutron irradiation experiments and Monte Carlo simulations with PHITS version 3.17 (Particle and Heavy Ion Transport code System). The results revealed that the quantities of both short-lived nuclides ( 24 Na and 56 Mn) were reduced to 1/25 of their original amount by the coating material when a coating of 10 mm thickness was applied. Furthermore, the material was effective in reducing the production of long-lived nuclides ( 60 Co, 152 Eu). Thus, this material can significantly reduce the environmental and economic burden associated with it. Highlights: A novel coating material for reduction of neutron activation was developed. The coating material is a polyurethane base material mixed with boron carbide. The low activation effect for concrete was evaluated through neutrons irradiation experiments and Monte Carlo simulations.